2016
DOI: 10.1103/physrevlett.116.037201
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Glass State of the Nearly Metallic Spinel Cobalt Vanadate

Abstract: Strain, magnetization, and unpolarized and polarized neutron diffraction measurements were performed to study the magnetic and structural properties of spinel CoV2O4. Magnetostriction measurements indicate that a subtle distortion of the crystal along the direction of magnetization, ∆L/L ∼ 10 −4 , exists and varies from elongation to contraction in a second order fashion upon cooling. Unpolarized and polarized single-crystal neutron experiments indicate that upon cooling the ferrimagnetic structure changes fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 31 publications
5
38
0
Order By: Relevance
“…For CoV 2 O 4 , the previous reports of the experimental studies in the single-crystalline and polycrystalline samples suggested the presence of additional transition within the ferrimagnetic phase [ 34,35,38,39 ]. However, the reported transition temperatures, also including the ferrimagnetic transition temperature T C , differ from study to study.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…For CoV 2 O 4 , the previous reports of the experimental studies in the single-crystalline and polycrystalline samples suggested the presence of additional transition within the ferrimagnetic phase [ 34,35,38,39 ]. However, the reported transition temperatures, also including the ferrimagnetic transition temperature T C , differ from study to study.…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 1(*) depicts the ferrimagnetic transition temperature T C and two other transition temperatures T 1 and T 2 in Co 1+x V 2−x O 4 as functions of off-stoichiometry x (the solid lines), which were suggested from the magnetization and magnetostriction measurements [ 39 ]. By increasing the amounts of the off-stoichiometry x, T C increases but T 1 and T 2 decrease.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations